PENGARUH STRUKTUR KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KEBIJAKAN HUTANG PERUSAHAAN STUDI KASUS PERUSAHAAN MANUFAKTUR SUB SEKTOR OTOMOTIF TERDAFTARDI BURSA EFEK INDONESIA - Laila Rahmawati Oetari; Emilia Gustini; Lukita Tripermata (Universitas Indo Global Mandiri)
This study aims to determine how the influence of Manajerial Ownership and Institutional Ownership Against Corporate Debt Policy in Manufacturing sector otomotif of Company in Indonesia Stock Exchange. This study uses multiple linear regression analysis method, variables used in this study is the Manajerial Ownwership (X1) and Institutional Ownership (X2) are hypothesized to affect the not Debt Policy (Y). 9 companies listed in BEI are the samples of this study. ICMD 2012 till 2015 is used as a data collector. Based on the results of multiple linear regression analysis obtained Manajeial Ownership and Institutional Ownership non significantly parcial and simultan insfluences the policy of the company debts.The result shows, In an effort to increase debt policy (DER), the company can increase the company's net profit, so that the company can meet its short-term and long-term obligations, the company will use internal funds much more than using the debt, It is expected that companies should be able to control their expenditures effectively against debt policy.Keywords : Manajerial Ownership, Institutional Ownership, Debt Policy